2020
DOI: 10.1038/s41394-020-00334-w
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality and secondary complications four years after traumatic spinal cord injury in Cape Town, South Africa

Abstract: Study design A prospective, regional, population-based study.Objectives (1) Determine the mortality rate and factors associated with it 4 years after a TSCI and (2) The point prevalence of secondary medical complications of survivors at 4 years. Setting Communities of the Cape metropolitan area, South Africa. Methods All persons (n = 145) sustaining a TSCI from 15 September 2013 to 14 September 2014 were eligible for followup at 4 years. Participants were contacted after 4 years. The next of kin, via verbal au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…The participants experienced a range of SHCs, but the most prevalent SHC was pain (94%). Pain is the most pervasive and significant problem throughout a person’s lifespan with SCI (Madasa et al 2020 ; Piatt et al 2016 ). When patients report pain symptoms their focus is not on the severity and the location of the pain but the different facets of life affected by pain, namely mental health, physiological impairments and personal behaviour (Müller et al 2017 ; Yorkston et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The participants experienced a range of SHCs, but the most prevalent SHC was pain (94%). Pain is the most pervasive and significant problem throughout a person’s lifespan with SCI (Madasa et al 2020 ; Piatt et al 2016 ). When patients report pain symptoms their focus is not on the severity and the location of the pain but the different facets of life affected by pain, namely mental health, physiological impairments and personal behaviour (Müller et al 2017 ; Yorkston et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were afraid to leave their homes because of the fear of bladder and bowel leakage. Bowel and bladder problems are problematic SHCs in people with SCI (Piatt et al 2016), with a prevalence of 44% bladder dysfunction and 42% bowel dysfunction 4 years post-SCI in South Africa (Madasa et al 2020). A study conducted in Ghana reported that patients with SCI did not want to participate in social events, such as weddings because of bowel and bladder http://www.sajp.co.za Open Access incontinence for fear of leakage in public.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations